Comparison of Nutritional and Bioactive Component in Graded Highland Barley Flour - Chongyu LI; Bin DANG; Falin ZHANG; Xijuan YANG (Shipin gongye ke-ji)
To elucidate the chemical composition differences and processing applications of three types flour fractions produced in highland barley milling, a comparative analysis of their nutritional and functional components was conducted in this study. The results showed that there were significant differences (P<0.05) in the content of nutritional and functional components among the three graded flours of highland barley. Among them, the protein (11.24%), total dietary fiber (39.72%), arabinoxylan (16.95%), and total amino acids (14.62%) levels of highland barley coarse bran powder were relatively the highest. Additionally, the highland barley coarse bran powder was also rich in minerals such as potassium, magnesium, calcium, and phenolic substances. The content of fat (3.68%) and β-glucan (4.92%) in highland barley fine bran powder was relatively the highest, while the content of total starch (80.40%) in highland barley flour was the highest. Glutamic acid was the amino acid with the highest content among the three graded flours. The primary limiting amino acid for coarse bran powder and flour was lysine, while for fine bran power it was threonine. A total of 13 phenolic acids and 8 flavonoids were detected across the three graded flours. The polyphenols in highland barley coarse and fine bran powder were mainly composed of bound coumaric acid and hesperidin, while the polyphenols in flour were mainly composed of bound gallic acid and rutin. In summary, the three types flour fractions had different nutritional compositions, which would effect their potential applications. Overall, coarse bran of highland barley could be utilized for the development of foods rich in dietary fiber, amino acids, minerals, and polyphenolic compounds, while fine bran can serve as a source material for β-glucan extraction. This research can provide a theoretical basis for the processing and utilization of graded highland barley flour.